2022
DOI: 10.3390/coatings12020158
|View full text |Cite
|
Sign up to set email alerts
|

Towards Investigating Surface Quality of Single-Crystal Silicon Optics Polished with Different Processes

Abstract: A series of cleaning and etching experiments utilizing organic solvent or weak alkali solutions were performed on single-crystal silicon optics polished with different processes. Polishing-introduced fractured defects in the subsurface layer were systematically characterized using laser-induced scattering imaging and photothermal weak absorption imaging techniques. A white-light interferometer also measured the surface morphology and roughness of the samples to evaluate the surface quality of the optics. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…With the increase in H 2 O 2 concentration, the roughness value of the FS surface gradually decreases, and it reduces to ~0.35 nm as the H 2 O 2 concentration increases to 20%, indicating a reduction in roughness of ~25%. Generally, the reduction in surface roughness is caused by the surface corrosion and reduction in surface defects [48][49][50]. Thus, based on the results from Figures 1 and 7, the treatment with the H 2 O 2 solution can not only affect the surface water adsorption and change the hydrophilicity of the FS surface, partial H 2 O 2 may penetrate into the subsurface and corrode the FS surface to some extent.…”
Section: Suppressed Topography Of Various Fs Surfacesmentioning
confidence: 92%
See 1 more Smart Citation
“…With the increase in H 2 O 2 concentration, the roughness value of the FS surface gradually decreases, and it reduces to ~0.35 nm as the H 2 O 2 concentration increases to 20%, indicating a reduction in roughness of ~25%. Generally, the reduction in surface roughness is caused by the surface corrosion and reduction in surface defects [48][49][50]. Thus, based on the results from Figures 1 and 7, the treatment with the H 2 O 2 solution can not only affect the surface water adsorption and change the hydrophilicity of the FS surface, partial H 2 O 2 may penetrate into the subsurface and corrode the FS surface to some extent.…”
Section: Suppressed Topography Of Various Fs Surfacesmentioning
confidence: 92%
“…Previously, the chemical etching [50], reactive ion etching Previously, it was reported that after traditionally grinding and polishing processes, a polishing redeposition layer with traceless photoactive impurities (such as ceria and iron) can exist on the top surface layer with a thickness of ~50 nm [51]. These surface defects can be migrated or removed by chemical etching [50], reactive ion etching [48], or a combined etching process [49]. The photoactive impurities at the near-surface region of FS can also be leached out of glass during the immersion in strong acid and/or H 2 O 2 solutions [50].…”
Section: Suppressed Topography Of Various Fs Surfacesmentioning
confidence: 99%
“…Prior to dry etching, we cleaned the surface area of the optical element using organic solvents to remove dust, oil, and impurities [ 32 , 33 ]. During the dry etching process, we employed three etching processes to remove the damage precursors on the surface of the optical element, based on previous etching experience.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, based on the above analysis, we chose the following three research programs to study the dry etching process, and the specific etching process is shown in Table 2. Prior to dry etching, we cleaned the surface area of the optical element using organic solvents to remove dust, oil, and impurities [32,33]. During the dry etching process, we employed three etching processes to remove the damage precursors on the surface of the optical element, based on previous etching experience.…”
Section: Methodsmentioning
confidence: 99%
“…This technique reacts to the defects on the surface or sub-surface of the sample by measuring the weak thermal absorption values of the localized area. A photothermal weak absorption imaging system based on PCI technology was used to study absorption defects on the sample surface [30]. 1 W quasi-continuum laser (3.8 µm) was used as the pump beam and a 5 mW He-Ne laser (632.8 nm) was used as the detection beam.…”
Section: Photothermal Weak Absorption Analysismentioning
confidence: 99%